Residential trade and industry: European market analysis, future trends and influencing factors - Roberto Cervelló-Royo; Francisco Guijarro Martínez; Thomas Pfahler; Marion Preuss (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2015)
[Preface] Residential trade and industry assets are a basic need of individuals with the result of assessing housing as a right in several nations all over the world. Though there is a strong focus on the relationship between populations and housing demands, there is no direct interaction between them for two reasons: it is mainly households and not individuals that require real estate and, secondly, the needs of households change over time. Therefore, various correlations can be identified in order to clarify the movements detected in housing asset stock on a foundation of household characteristics as well as population and society performance structures. The analysis of housing stock in terms of demographic development is important for gaining an in-depth understanding of housing tendencies, general characteristics and underlying economic factors. In the present volume of the FOM Arbeitspapiere the authors establish a market and trend analysis of the European member countries on the basis of specified criteria. Thus they identify numerous streams as well as analogical tendencies.
Keywords: 330; Wohnungsmarkt; Immobilienwirtschaft; EU-Staaten